Analysis of Supervision Strategy on Company Operations in Achieving Good Service to Customers (Case Study at PDAM Tirtanadi, North Sumatra, Cemara Branch, Medan) - Anastasya Br Ginting; Wahyu Syarvina (Fakultas Ekonomi Universitas Dehasen Bengkulu, 2022)
Regional Drinking Water Company Tirtanadi North Sumatra Cemara Medan Branch as one of the marketing branches of PDAM Tirtanadi North Sumatra Province which serves customers in the District of Medan Deli, East Medan and Percut Sei Tuan. The Cemara Branch, apart from serving clean water customers, also serves wastewater. The number of drinking water customers of the Cemara Branch to date is 18,643 NPA, clean water sales revenue until December 2021 is Rp. 2,787,032,554.5 and 495,548 M3 cubication. In achieving company goals, strategy as a way of maximizing company operations at PDAM Tirtanadi, North Sumatra, Cemara Medan Branch, in the field of supervision makes a good work program plan that is adapted to environmental conditions which will later become a race and target so that it can achieve good company operations and as well as customer service. The author examines how the role and supervision system implemented by PDAM Tirtanadi, North Sumatra, Cemara Medan Branch in achieving good service to customers? and What are the obstacles that often occur in operating supervision at PDAM Tirtanadi, North Sumatra, Cemara Medan Branch?. The research method used is descriptive research method with a qualitative approach which aims to describe and describe systematically, accurately about the facts and phenomena that exist at the research site, namely PDAM Tirtanadi, North Sumatra, Cemara Branch, Medan. Data collection techniques used in this study were obtained through interviews and literature studies from previous studies and documents. As resource persons, namely the head of the section and the staff in the supervision section. As a result of the research conducted, it can be seen that in the implementation of supervision and strategies carried out by the supervisory department it is good and running in accordance with the work program planning that has been determined, where the work program is one of the strategies that can be used as a reference to continue to run the company's operations in accordance with with the corporate vision and mission of PDAM Tirtanadi, North Sumatra, Cemara Medan Branch.